A new Precedent in Health Cooperation to Make an Assessment Model of Total Demand for Health Service - Bassel; Dana; Mohammad; Zahraa (Magyar Gerontológia, 2025)
Working in a team greatly improves health cooperation and helps propose innovative solutions for health issues. Furthermore, a multidisciplinary team has more overlapping roles defined by communication and troubleshooting.